PELATIHAN MEMBUAT LILIN AROMATERAPI DENGAN MEMANFAATKAN LIMBAH MINYAK GORENG - Munthia, Sekar Ayu; Haqiyah, Aridhotul; Iskandar, Tatang (Universitas Islam 45 Bekasi, 2024)
This program aims to introduce an efficient way to manage cooking oil waste in Karangmulya Village through interviews, observations, training, and hands-on practice to housewives. The subjects of this program are housewives of Karangmulya Village who will manage the cooking oil waste by producing aromatherapy candle products. The main objective is to optimize the management of cooking oil waste and produce quality products. This program takes the main raw material of cooking oil available in every home, with the aim of introducing innovative ways to turn it into value-added aromatherapy candles. The implementation method applies socialization and hands-on training in making aromatherapy candles. The results of the service are a better understanding of the right and effective way to utilize cooking oil waste for making aromatherapy candles, so that the participants of the activity can turn household waste into a potential source in creating value-added products and reducing the impact of environmental pollution.